The nexus between servant leadership and organizational citizenship behavior through the mediating role of perceived organizational politics in Ethiopian federal public service organizations - Addisu Debalkie Demissie; Abebe Ejigu Alemu; Assefa Tsegay Tensay (Cogent Business & Management, 2024)
This is a study about the servant leadership-organizational citizenship behavior debate aimed at examining the effect of servant leadership on organizational citizenship behavior through the mediating effect of perceived organizational politics. An explanatory research design and quantitative approach were employed. In the Ethiopian federal public sectors, data were collected using a standard questionnaire from 321 respondents. The present study employed social learning theory and social exchange theory to underpin the mechanism how perceived organizational politics mediates the effect of servant leadership on organizational citizenship behavior. To test hypotheses, the study employed structural equation modeling using AMOS software version 26. The findings of the study established that servant leadership has a positive and statistically significant effect on organizational citizenship behavior. In addition, servant leadership has a negative and statistically significant effect on perceived organizational politics. Likewise, perceived organizational politics have a negative and statistically significant effect on organizational citizenship behavior. As it is hypothesized, the finding of the structural equation analysis demonstrated that Perceived organizational politics mediated the effect of servant leadership on organizational citizenship behavior. This study is the first empirical study to use perceived organizational politics as a mediating role between servant leadership and organizational citizenship behavior.Discover how leaders' selfless service and employees' positive contributions can shape a better work environment in Ethiopian public service organizations. This research delves into the link between servant leadership, organizational citizenship behavior, and the effect of perceived organizational politics. By examining these factors, we gain insights into how leaders' servant behavior can influence employees' willingness to go extra their job requirements. Ultimately, this study seeks to promote a culture of servant leadership, fostering trust, collaboration, and organizational effectiveness. By shedding light on these dynamics, we hope to inspire leaders and policymakers in Ethiopia and beyond to adopt practices that enhance employee engagement, and public service delivery.
Keywords: 650; Servant leadership; organizational citizenship behavior; perceptions of organizational politics; public service organizations; Ethiopia